2016
DOI: 10.2527/jas.2015-9484
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and direct effects for Charolais-sired calf weight and growth, cow weight and weight change, and ratios of cow and calf weights and weight changes across warm season lactation in Romosinuano, Angus, and F1 cows in Arkansas1

Abstract: The use of Brahman in cow-calf production offers some adaptation to the harsh characteristics of endophyte-infected tall fescue. Criollo breeds, such as the Romosinuano, may have similar adaptation. The objectives were to estimate genetic effects in Romosinuano, Angus, and crossbred cows for their weights, weights of their calves, and ratios (calf weight:cow weight and cow weight change:calf weight gain) across lactation and to assess the influence of forage on traits and estimates. Cows ( = 91) were bred to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Bolormaa et al [ 11 ] also reported higher heritability estimates for RFI (0.36), in a study with nine herds of Bos Taurus , Bos indicus , and crossbreeds. Also, Silva et al [ 35 ] reported similar heritability estimates for ADG (0.39±0.08) and DMI (0.43±0.08) in a study using the same experimental population. The results of this study pointed out that there is genetic variability in selecting for feed efficiency indicator traits in Nellore cattle.…”
Section: Resultsmentioning
confidence: 58%
“…Bolormaa et al [ 11 ] also reported higher heritability estimates for RFI (0.36), in a study with nine herds of Bos Taurus , Bos indicus , and crossbreeds. Also, Silva et al [ 35 ] reported similar heritability estimates for ADG (0.39±0.08) and DMI (0.43±0.08) in a study using the same experimental population. The results of this study pointed out that there is genetic variability in selecting for feed efficiency indicator traits in Nellore cattle.…”
Section: Resultsmentioning
confidence: 58%
“…Mucus glycoproteins are least abundant in the duodenum and jejunum, which contributes the movement of digesta across intestinal walls [ 51 ] and increases its availability. Most carbohydrates are simultaneously absorbed in the proximal part of the small intestine [ 104 ], which significantly contributes to the absorption, accumulation and, probably, biotransformation of mycotoxins in enterocytes [ 81 , 105 ]. Published data relating to those processes and the involved intestinal segments are incomplete and often contradictory.…”
Section: Activity Of Zenmentioning
confidence: 99%
“…Several breeders in the Mexican tropics have used Romosinuano due to ease of management, longevity (Carroll et al, 2011;, fertility (Riley et al, 2007), tolerance to heat, humidity (Scharf et al, 2010), and to the toxic effects of endophytes commonly present in tall fescue (Riley et al, 2016). The Asociación Mexicana de Criadores de Ganado Romosinuano y Lechero Tropical (AMCROLET) was established in 1998 (De Alba, 2011), and it is responsible for the herdbook and the performance records.…”
Section: Introductionmentioning
confidence: 99%